2022
DOI: 10.1108/jbim-11-2020-0487
|View full text |Cite
|
Sign up to set email alerts
|

Supply chain finance in enhancing supply-oriented and demand-oriented performance capabilities – moderating role of perceived partner opportunism

Abstract: Purpose While supply chain scholars concur on the need to integrate supply chain finance (SCF) processes to meet ever-changing customer demands, it is unclear how SCF influences business performance in the presence of perceived opportunistic behavior. Therefore, the study aims to investigate the moderating role of perceived partner opportunism in the supply chain. Design/methodology/approach Drawing on the dynamic capability theory (DCT), this study investigates how perceived supply chain partner opportunism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 101 publications
1
8
0
Order By: Relevance
“…Among the various characteristics, enterprise size (measured by the number of employees) and the company's operating period (measured by the number of years since the firm was established) were controlled. This is because larger or older firms may be more likely to obtain SCF than small or young firms (Rajaguru et al ., 2022). Annual sales and total assets can demonstrate a firm's profitability and asset reserve, thereby reflecting the firm's demand for SCF.…”
Section: Methodsmentioning
confidence: 99%
“…Among the various characteristics, enterprise size (measured by the number of employees) and the company's operating period (measured by the number of years since the firm was established) were controlled. This is because larger or older firms may be more likely to obtain SCF than small or young firms (Rajaguru et al ., 2022). Annual sales and total assets can demonstrate a firm's profitability and asset reserve, thereby reflecting the firm's demand for SCF.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several studies have taken the DCT perspective to examine the business organizational structure and design capabilities integration with social media (e.g., [165], [166]).…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…This is significant because it is found that delayed payments are a great concern to MSMEs, which have constrained factoring services to discount their bills (Bose, 2013). Rajaguru et al (2022) found a sequentially mediating relationship between supply-and demand-oriented performances with SCF and business performance. Studies such as Hofmann et al(2019), Vu et al (2022) and Bi et al (2022) also found that SCF significantly affects supply chain financing and organisational performance.…”
Section: Introductionmentioning
confidence: 98%